Development of an Immunochromatographic Strip for Rapid Detection of Mink Enteritis Virus - Lin, Peng; Wang, Jianke; Song, Shanshan; Cheng, Yuening; Yi, Li; Cheng, Shipeng; Wang, Zhenjun (Frontiers in Microbiology, 2022)
Although mink enteritis virus (MEV) is an acute, virulent, and highly contagious pathogen in minks, there is currently a lack of a quick diagnostic method. By conjugating colloidal gold nanoparticles with the MEV-specific monoclonal antibody, MAb 14, we developed a single-step competitive immunochromatographic strip (ICS) assay for simple determination of MEV. The optimal concentrations of the colloidal gold-coupled MAb 14 (coating antibody), the capture protein (MEV VP2 protein), and the goat anti-mouse antibody were 1.0 mg/ml, 0.8mg/ml, and 1.0 mg/ml, respectively. The limit of detection was approximately 512 hemagglutination units/100μl of MEV B strain. Other common viruses of mink were tested to evaluate the specificity of the ICS, and the results showed no cross-reactivity for other pathogens. In comparison with the Anigen Rapid CPV Ag Test Kit (BioNote, Korea) in testing 289 mink samples, the percentage of agreement and relative sensitivity and specificity of the MEV ICS assay were 94.1%, 93.2%, and 97.1%, respectively. The ICS test was found to be a sufficiently sensitive and specific detection method for the convenient and rapid detection of MEV.